Epidemiological investigation and prevention and control strategies of rubella in Anhui province, China, from 2012 to 2021 - Zhang, Ning; Cheng, Xiaodong; Zhou, Shujie; Wang, Binbing; Luo, Xianwei; Chai, Yu; Tang, Jihai; Su, Bin; Liu, Zhirong (Frontiers in Public Health, 2022)
Abstract Background Rubella is a highly contagious viral infection with mild manifestations that occurs most often in children and young adults. infection during pregnancy, especially during the first trimester, can result in an infant born with congenital rubella syndrome (CRS). The purpose of this paper is to analyze the characteristics of rubella epidemics in Anhui province from 2012 to 2021 and explore the prevention and control strategies of rubella. Methods A descriptive epidemiological approach was used to examine the epidemiological characteristics of rubella in Anhui Province between 2012 and 2021. Results From 2012 to 2021, a total of 4987 cases of rubella were reported in Anhui province, with an average annual incidence of 8.11 per million, demonstrating an overall downward trend (χ2 trend =3141.06, P <0.01). The average yearly incidence of rubella in southern Anhui, central Anhui, and northern Anhui were 9.99 per million, 11.47 per million, and 4.50 per million, respectively, with statistically significant differences (χ2 =792.50, P <0.01). (χ2 =792.50, P <0.01). The male to female incidence ratio was 1.67:1, and the male incidence rate was higher than the female incidence rate. Most cases occurred among students, accounting for 56.59% of all cases, and the 10-34 age group accounted for approximately 73.71% of all cases. Regarding immunization history, 3.57% of cases had two doses or more, 6.62% had one dose, 16.40% had none, and the remainder were uncertain. Conclusions The incidence of rubella in Anhui province from 2012 to 2021 continued to decline, with regional variations observed. The 10-34-year-old population without a history of rubella vaccination is at high risk for the disease. It is suggested to carry out rubella vaccination and congenital rubella syndrome monitoring according to the actual situation.